PELATIHAN PEMODELAN NILAI RELIABILITAS ROTATING EQUIPMENT DI PT. PERTAMINA HULU ROKAN, PEKANBARU, RIAU - Jayatun, Yohanes Agus (ReTII, 2024)
This community service activity is a collaboration between the Yoyakarta National Institute of Technology (ITNY) and PT. Pertamina Hulu Rokan (PHR) moderated by Solid Corporotaion. The activity was held at the Pertamina Hulu Rokan (PHR) Training Center in Pekanbaru, Riau, from May 22 to 24, 2023, in the form of short course. The purpose of this activity is to increase the knowledge of engineers at PT. PHR on the method of assessing the reliability of rotating equipment based on reliability value. The course materials are basic maintenance theory and mathematical model for calculating equipment reliability value. After learning the theory, participants were divided into groups. Each group was given the task of calculating the reliability of the rotating equipment unit. The selected unit must be a unit handled by at least one member. The results of each group’s assignment were presented in front of all course participants to be discussed. The participants’ knowledge and understanding of the reliability of industrial equipment increased sharply after participating in this course. The increase can be seen from the average post-test results which are much higher than the average score of pre-test results. A simple theoretical presentation followed by tasks that must be done in groups is the main factor in the success of this community service activity.